Isolasi Antioksidan Tumbuhan Sarang Semut (Myrmecodia pendens Merr & Perry) Asal Papua (Journal of Tropical Pharmacy and Chemistry, 2025)
Research about active antioxidant compounds isolated from plants ant nests (Myrmecodia pendens Merr. & Perry) from Papua by the method of column chromatography has been done. This study aimed to explore the isolation of the active class of compounds as antioxidants from ant nest plant. Isolates obtained using the method of column chromatography and antioxidant activity of the ant nest plants isolates tested used spraying method with free radical DPPH (2,2-diphenyl-1-picrylhydrazyl) after eluted on thin-layer chromatography. At separation by column chromatography, eluate collected in vials with a volume of 10 ml. Based on the results of fractionation, separation of the components obtained by 74 vials. Identification using TLC by determining the Rf value of each component. The same Rf value is considered as a single fraction. Based on the results obtained seven fractions TLC. Active isolates (F6) obtained by spraying. The results of fraction of spot with DPPH staining showed that the isolates was considered the most active isolates as seen from the formation of a yellow color that is lighter and more dominant than the other fractions, this indicates that the fraction (F6) binds more free radicals (DPPH).